Mapping of Collected Plants Grown in Waru-Waru and Teluk Semut Costal at Sempu Island, Malang, Indonesia - Irawanto, Rony; Rahandiantoro, Apriyono; Mudiana, Deden (Proceeding International Conference on Global Resource Conservation, 2015)
The Purwodadi Botanic Garden main duty is ex-situ plants conservation, especially from dry lowland area. Conservation can be carried through the exploration and collecting the plants diversity in an priority area The selected area for plants exploration activities in next several years are small islands. Sempu Island is selected a small island. AlsoSempu Island have status as nature reserve with a diversity of ecosystems such as mangrove forests, coastal forests, lowland forests and grasslands, as well as the diversity of flora and fauna that are endemic and unique. Based on some research previously the plants diverisity of Sempu Island are 282 species included in 80 families at 10 blocks location, namely: Telaga Lele, Telaga Sat, Telaga Dowo, Gladakan, Baru-baru, Gua Macan, Teluk Raâas, Teluk Semut, Air Tawar, and Waru-waru. This study aims to show the mapping of collected plantsÂ from exploration in Waru-Waru and Teluk Semut Coastal in Sempu Island. mainly at two site locations are Waru-Waru and Teluk Semut that separeted into two team. This is done as a basis for planning activities in the exploration and collecting Sempu Island the following year. After conducting flora exploration of the plant collected are 274 numbers (1.106 plants material) with scientific name are 111 species. Some plant were found and collected by every team are same, around 24 species and 21 families.The new plants collection for Purwodadi Botanic Garden are 21 species. The plant collected from exploration of flora are mapping to see coverage exploration area and this picture can give us undestanding the other area could be explore. From result know that exploration flora in 2015 year Â still on the coastal around the northern part of the island Sempu.Keywords: Exploration; mapping; plants; Sempu IslandÂ